Fourier transform infrared studies of the N2-O2 binary system: Cryocrystals
Solid solutions (N2)x(O2)1–x have been investigated by infrared absorption measurements mainly in the O2 and N2 stretching regions, between 60–10 K, completing former similar studies by Raman scattering. We produced thermodynamically stable samples by a careful thermal treatment, followed by cooling/heating cycles over weeks, during which we took spectra. From fingerprints in infrared spectra we deduce phase transition lines, solubility lines and suggest a refined, improved T–x% phase diagram with respect to inconsistencies between those in literature. Spectra of N2–O2 mixtures are pretty complex but referring to known spectra of pure systems N2 or O2 we were able to assign and interpret broad ( 100 cm–1) phonon side bands to fundamentals and electronic transition (O2) depending on actual temperature and concentration. Narrow features in spectra (